Science Fusion in Contemporary Mexican Literature - Chandler, Brian T (Bucknell studies in Latin American literature and theory, 2024)
Science Fusion draws on new materialist theory to analyze the relationship between science and literature in contemporary works of fiction, poetry, and theater from Mexico.In this deft new study, Brian Chandler examines how a range of contemporary Mexican writers "fuse" science and literature in their work to rethink what it means to be human in.